Is There Any Benefit of Neuromonitoring during Descending and Thoracoabdominal Aortic Aneurysm Repair?. Issue 5 (September 2015) - Fok, Matthew; Jafarzadeh, Fatemeh; Sancho, Elena; Abello, David; Rimmer, Lara; Howard, Callum; Kennedy, Tom; Hammoud, Ibrahim; Bashir, Mohamad
Objective: Paraplegia remains the most feared and a devastating complication after descending and thoracoabdominal aneurysm operative repair (DTA and TAAAR). Neuromonitoring, particularly use of motor-evoked potentials (MEPs), for this surgery has gained popularity. However, ambiguity remains regarding its use and benefit. We systematically reviewed the literature to assess the benefit and applicability of neuromonitoring in DTA and TAAAR. Methods: Electronic searches were performed on 4 major databases from inception until February 2014 to identify relevant studies. Eligibility decisions, method quality, data extraction, and analysis were performed according to predefined clinical criteria and end points. Results: Among the studies matching our inclusion criteria, 1297 patients had MEP monitoring during DTA and TAAAR. In-hospital mortality was low (6.9% ± 3.6). Immediate neurological deficit was low (3.5% ± 2.6). In one third of patients (30.4% ± 14.2), the MEPs dropped below threshold, which were 30.4% and 29.4% with threshold levels of 75% and 50%, respectively. A range of surgical techniques were applied after reduction in MEPs. Most patients whose MEPs dropped and remained below threshold had immediate permanent neurological deficit (92.0% ± 23.6). Somatosensory-evoked potentials were reported in one third of papers with little association between loss of somatosensory-evoked potentials and permanent neurological deficit (16.7% ± 28.9%). Conclusions: We demonstrate that MEPs are useful at predicting paraplegia in patients who lose their MEPs and do not regain them intraoperatively. To date, there is no consensus regarding the applicability and use of MEPs. Current evidence does not mandate or support MEP use.